Recontextualisation in museum displays: refracting discourses over time - Rall, Medee (School of Education, 2019)
This research investigates the representation of people in museums, focusing on the San, South Africa’s first nation. Using a multimodal social semiotic framework, it analyses three exhibitions of the San that were mounted over a period of a hundred years in a natural history museum from 1911 to the present. The research takes into consideration the socio-political background in which the exhibitions were designed, and examines how this manifests in the ways in which the San were represented. The analysis surfaces three dominant discourses, namely evolutionary, ecological as well as a discourse of transformation. These discourses are complex and always in dialogue with one another. The research entailed working with and analysing photographs and drawing on secondary texts of two exhibitions that are no longer open to the public, and analysing an existing exhibition. The data analysis was framed by the semiotic principles of recontextualisation as posited by Bezemer and Kress (2008): selection, social relations and arrangement. Selection refers to the choice of meaning materials for an exhibition. Arrangement refers to the decisions made in the display of the meaning materials (including layout, framing, and foregrounding), and social relations pertain to the social repositioning that takes place in the process of recontextualisation. The research showed how discourses shifted across time, but that dominant discourses such as an evolutionary discourse persisted through the ages and the various exhibitions. By analysing exhibitions of the San against the political backdrop of colonialism, apartheid and post-apartheid this research contributes to an understanding of colonial museums and their exhibitions. It provides suggestions to South African museum practitioners dealing with colonial collections on how to bring a decolonial perspective to exhibitions. The insights gained through this research may enable museum professionals to better understand meaning making and representation in museum display and to contribute to current debates on representation, including ways in which dominant discourses are reflected and refracted in museums. The dialogue between discourses and traces of discourse is of interest within the museum context as well as other contexts of transformation. The research shows that it is possible to map a re-imagining of museum display on the three principles of recontextualisation – selection, arrangement and social relations – in order to see what forms transformation in museum display could take.